1983
DOI: 10.1007/bf00541230
|View full text |Cite
|
Sign up to set email alerts
|

A fibroblast mitogen present in scleroderma but not control sera: Inhibition by proteinase inhibitors

Abstract: Fibroblast mitogenic activity (MA) has been identified in scleroderma (SD) sera. Control and scleroderma skin fibroblasts in early passage were observed for replication (cell counts) after 72 h of serum exposure. SD sera at 15% concentration induced a significant increase in control fibroblast numbers when compared with control sera; this effect was not seen with SD cells while at higher serum concentrations (30%); SD cells were slightly responsive to the MA. MA was completely abrogated by the proteinase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This evidence for different subpopulations of fibroblasts in scleroderma skin prompted additional studies, and even in normal skin some demonstrated different clones of fibroblasts characterized by a high or low synthesis of collagen. In addition, when normal fibroblasts were grown in the presence of serum obtained from scleroderma patients these activated subclones were preferentially stimulated [30]. However, identification of these clones in vivo is difficult and there are only few attempts to develop markers recognizing distinct fibroblast subpopulations.…”
Section: Smentioning
confidence: 98%
“…This evidence for different subpopulations of fibroblasts in scleroderma skin prompted additional studies, and even in normal skin some demonstrated different clones of fibroblasts characterized by a high or low synthesis of collagen. In addition, when normal fibroblasts were grown in the presence of serum obtained from scleroderma patients these activated subclones were preferentially stimulated [30]. However, identification of these clones in vivo is difficult and there are only few attempts to develop markers recognizing distinct fibroblast subpopulations.…”
Section: Smentioning
confidence: 98%